Breathing valve composite membrane as well as preparation method and application thereof
By using composite diaphragms of polymer sheet layer and fluoroelastic composite material layer in the breathing valve, the problem of high leakage amount of traditional breathing valve diaphragms is solved, low leakage amount and excellent high temperature resistance are achieved, and the requirements of international standards are met.
Patent Information
- Application Number
- CN202311165027.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-11
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-09-11
AI Technical Summary
The existing respiratory valve diaphragm has high leakage, high safety risks, and it is difficult to meet the leakage requirements of international standards.
A breathing valve composite diaphragm is provided, including a polymer sheet layer and a fluoroelastic composite material layer, through specific raw material combination and preparation processes, the high temperature resistance and yield deformation ability of the diaphragm are improved, thereby reducing leakage.
It achieves a low leakage volume of the breathing valve and has excellent high temperature resistance, which is far lower than the relevant standards for leakage volume of the existing breathing valve at home and abroad.
Smart Images

Figure CN119590052A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of breathing valve sealing, and in particular to a breathing valve composite diaphragm and a preparation method and application thereof. Background Art
[0002] A breathing valve is a valve that can not only ensure that the storage tank space is isolated from the atmosphere within a certain pressure range, but can also communicate with the atmosphere (breathe) when the pressure exceeds or falls below this pressure range. Its function is to prevent the storage tank from being damaged due to overpressure or vacuum, and at the same time reduce the evaporation loss of the storage medium. Setting a breathing valve can not only reduce the gas emission in the tank, thereby reducing the pollution to the atmosphere, but also prevent the storage tank from being damaged due to overpressure or instability due to ultra-vacuum, which plays a certain role in promoting safety and environmental protection.
[0003] At present, the design and research of breathing valve products in China mainly focuses on the gas flux above the opening pressure, while the gas leakage in the leakage range from 0.75 times the opening pressure to below the opening pressure of the breathing valve has not received much attention. In fact, with the development trend of centralization and large-scale development of storage tank areas, the gas leakage that has been ignored by people is very likely to lead to an increase in the concentration of flammable gases in the tank area, and increase the risk of fire and explosion. For this reason, the American Petroleum Institute (API) clearly stipulates in its breathing valve standard API Std2000 that the maximum leakage of breathing valves with a nominal diameter less than 150mm shall not exceed 0.014m per hour. 3 For breathing valves with a nominal diameter greater than 200 mm, the maximum leakage per hour shall not exceed 0.142 m 3 The most stringent international standard for leakage is the standard in some regions (enterprises) of Germany, which requires that the maximum leakage of breathing valves with a nominal diameter less than 150mm should not exceed 0.0017m per hour. 3 For breathing valves with a nominal diameter greater than 200 mm, the maximum leakage per hour shall not exceed 0.0045 m 3 . At present, the research and development of breathing valves in China mainly focuses on mechanical structures. However, due to the repeated opening and closing of the breathing valve during use, coupled with the large amount of corrosive components in the oil and gas, the mechanical seal is very easy to be damaged and fail, resulting in increased leakage. Therefore, a reasonable mechanical structure and an efficient sealing rubber diaphragm can be combined to achieve a long-term low leakage of the breathing valve. However, due to the limitations of diaphragm materials, my country's breathing valve industry standard SY / T0511-2010 stipulates that for breathing valves with a nominal diameter of less than 150mm, the maximum leakage per hour shall not exceed 0.04m 3 For breathing valves with a nominal diameter greater than 200 mm, the maximum leakage per hour shall not exceed 0.4 m 3The leakage volume is significantly higher than the current international standards. On the one hand, the high leakage volume increases the safety risk of my country's petrochemical storage tank area, which is a huge hidden danger to people's stable life. On the other hand, it also limits my country's domestic independent development path in the field of petrochemical oil and gas storage. Summary of the invention
[0004] The purpose of the present invention is to overcome the problem of high leakage and high safety risk of the conventional breathing valve diaphragm (gasket) in the prior art, and to provide a breathing valve composite diaphragm and its preparation method and application. The composite diaphragm provided by the present invention can achieve low leakage of the tank breathing valve and has excellent high temperature resistance.
[0005] In order to achieve the above-mentioned purpose, the present invention provides a breathing valve composite diaphragm on one hand, wherein the composite diaphragm comprises a polymer sheet layer and a fluororubber composite material layer, wherein the thickness of the polymer sheet layer is 0.1 to 1 mm; and the fluororubber composite material layer is made of a raw material composition containing fluororubber, inorganic filler, chopped fibers, an acid absorber, a vulcanizer, a release agent and a colorant.
[0006] Preferably, the polymer sheet material in the polymer sheet layer is selected from one or more of polyetheretherketone, polytetrafluoroethylene and polyimide.
[0007] Preferably, in the raw material composition, the fluororubber is type 26 fluororubber or type 246 fluororubber.
[0008] Preferably, in the raw material composition, the inorganic filler is selected from one or more of white carbon black, calcium silicate, magnesium silicate, aluminum silicate, calcium carbonate, barium sulfate, diatomaceous earth, graphite, silicon nitride and boron nitride.
[0009] Preferably, in the raw material composition, the chopped fibers are selected from one or more of aramid fibers, glass fibers, carbon fibers and ceramic fibers.
[0010] Preferably, the length of the chopped fibers is 1 to 5 mm.
[0011] Preferably, in the raw material composition, the acid absorber is selected from one or more of magnesium oxide, calcium oxide, zinc oxide and calcium hydroxide.
[0012] Preferably, in the raw material composition, the vulcanizing agent is selected from one or more of N,N'-dicinnamaldehyde-1,6-hexanediamine, 2,2-(4-hydroxyphenyl)hexafluoropropane, diisopropylbenzene peroxide and 2,5-dimethyl-2,5-di-tert-butylhexane peroxide.
[0013] Preferably, in the raw material composition, the release agent is selected from one or more of zinc stearate, ammonium stearate and paraffin.
[0014] Preferably, in the raw material composition, the colorant is selected from one or more of iron red, colloidal graphite and carbon black.
[0015] Preferably, in the raw material composition, the weight ratio of the fluororubber, the inorganic filler, the chopped fibers, the acid absorber, the vulcanizing agent, the release agent and the colorant is 100:10-60:10-30:0.001-20:0.001-5:0.2-2:0.001-3.
[0016] Preferably, the raw material composition further contains a vulcanization accelerator.
[0017] Preferably, the weight ratio of the fluororubber to the vulcanization accelerator is 100:0.001-2.
[0018] Preferably, the vulcanization accelerator is benzyltriphenylphosphonium chloride and / or triallyl isocyanurate.
[0019] Preferably, the thickness ratio of the polymer sheet layer to the fluororubber composite material layer is 1:1-4.
[0020] A second aspect of the present invention provides a method for preparing the composite diaphragm of a breathing valve, the method comprising:
[0021] (1) Preparation of fluororubber composite material: kneading the raw material composition, and then refining the obtained product multiple times to obtain a fluororubber composite material;
[0022] (2) Preparation of composite membrane:
[0023] The polymer sheet and the fluororubber composite material are thermally bonded and then vulcanized to obtain a composite diaphragm.
[0024] Preferably, in step (1), the mixing conditions include: temperature of 50 to 80° C., time of 15 to 60 min, and rotation speed of 20 to 60 rpm.
[0025] Preferably, in step (1), the refining conditions include: a temperature of 100 to 140° C., a refining number of 10 to 30 times, and a roller distance of 0.2 to 4 mm.
[0026] Preferably, in step (2), the conditions for thermal bonding include: a temperature of 150 to 160° C. and a time of 1 to 10 min.
[0027] Preferably, in step (2), the vulcanization conditions include: temperature of 180-240° C. and time of 8-24 hours.
[0028] The third aspect of the present invention provides a composite membrane for a breathing valve prepared by the method described above.
[0029] A fourth aspect of the present invention provides a composite diaphragm as described above or use of the composite diaphragm as described above as a sealing material for a breathing valve.
[0030] The breathing valve composite diaphragm provided by the present invention includes a polymer sheet layer of a specific thickness and a fluororubber composite material layer of a specific composition. The composite diaphragm has a good yield deformation in the leakage range from above 0.75 times the opening pressure of the breathing valve to below the opening pressure, thereby reducing the leakage of the breathing valve. At the same time, the breathing valve composite diaphragm provided by the present invention has excellent high temperature resistance.
[0031] Furthermore, the leakage of the composite diaphragm provided by the present invention at a temperature of 20°C and a tank breathing valve opening pressure of 0.75 times is: the leakage of the diaphragm used for the breathing valve with a nominal diameter of 150mm can be as low as 0.0002m per hour. 3 The diaphragm used in the breathing valve with a nominal diameter of 200mm can have a leakage rate as low as 0.0011m per hour. 3 , which is far lower than the existing domestic and foreign standards for the leakage of breathing valves. In the present invention, the "nominal diameter" refers to the nominal diameter of the breathing valve connection flange. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The present invention is a flow chart of preparing the composite diaphragm of the breathing valve. DETAILED DESCRIPTION
[0033] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0034] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0035] The first aspect of the present invention provides a composite diaphragm for a breathing valve, the composite diaphragm comprising a polymer sheet and a fluororubber composite material layer, wherein the fluororubber composite material layer is bonded to one side of the polymer sheet.
[0036] In the present invention, the polymer sheet layer supports the composite diaphragm to prevent the diaphragm from being too soft and sagging at the edge, which would cause leakage in the breathing valve. Lubricants and thermal conductors are added during pretreatment of the polymer sheet, which has good lubricity, thermal conductivity and friction resistance. The fluororubber composite material layer has good elasticity and appropriate elastic deformation, which enables the breathing valve to have excellent sealing performance. Compounding the polymer sheet layer and the fluororubber composite material layer can significantly reduce the leakage of the breathing valve.
[0037] In the present invention, the thickness of the polymer sheet layer should be appropriate. If it is too thick, the membrane will be hard as a whole, and the surface will be uneven and concave, and the effect of reducing the leakage of the breathing valve cannot be achieved.
[0038] In the present invention, the thickness of the polymer sheet is 0.1-1 mm. In a specific embodiment, the thickness of the polymer sheet can be 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm or 1 mm.
[0039] In the present invention, the polymer sheet refers to a material forming a polymer sheet. In a specific embodiment, the polymer sheet forming the polymer sheet can be a material well known to those skilled in the art. In a preferred embodiment, the polymer sheet in the polymer sheet can be selected from one or more of polyetheretherketone (PEEK), polytetrafluoroethylene (PTFE) and polyimide (PI).
[0040] In a specific embodiment, the polymer sheet layer is entirely formed of polymer sheets, and the polymer sheets need to be pre-treated before use. The pre-treatment includes: adding lubricants and thermal conductive agents to enhance the lubricity, thermal conductivity and anti-friction properties, and performing surface treatment on the polymer sheets.
[0041] The inventors have found through research that in the present invention, the composite diaphragm composed of a fluororubber composite material layer prepared from a raw material containing fluororubber and the polymer sheet layer can be used as a breathing valve sealing material to significantly reduce leakage.
[0042] In the present invention, the fluororubber composite material layer is made of a raw material composition containing fluororubber, inorganic filler, chopped fibers, an acid absorber, a vulcanizing agent, a release agent and a colorant. The fluororubber composite material layer is obtained by mixing, refining, thermal bonding and vulcanization of the raw material composition. Adding chopped fibers to the fluororubber composite material layer can maintain the dimensional stability of the composite diaphragm and increase the deformation recovery ability, thereby improving the high temperature resistance.
[0043] In the present invention, the fluororubber can be any fluororubber known in the art, as long as it can maintain the gasket shape and mechanical strength in an oil, acid or alkali environment. In a specific embodiment, in the raw material composition, the fluororubber can be 26-type fluororubber and / or 246-type fluororubber.
[0044] In the present invention, the inorganic filler can be a conventional choice in the art, as long as it can fill the rubber. In a preferred embodiment, in order to make the diaphragm have a good yield deformation in the leakage range of 0.75 times the opening pressure of the breathing valve to below the opening pressure, and further reduce the leakage of the breathing valve, in the raw material composition, the inorganic filler is selected from one or more of white carbon black, calcium silicate, magnesium silicate, aluminum silicate, calcium carbonate, barium sulfate, diatomaceous earth, graphite, silicon nitride and boron nitride.
[0045] In the composite membrane of the present invention, the chopped fibers may be various fibers well known to those skilled in the art. In a preferred embodiment, the chopped fibers are selected from one or more of aramid fibers, glass fibers, carbon fibers and ceramic fibers.
[0046] Specifically, the length of the chopped fibers may be 1 to 5 mm.
[0047] In the present invention, the acid absorber refers to an additive capable of absorbing acidic substances released during the preparation of the fluororubber composite material. The acid absorber can be a conventional choice in the art, as long as it can absorb the acidic substances released during the preparation of the fluororubber composite material. In a preferred embodiment, in the raw material composition, the acid absorber is selected from one or more of magnesium oxide, calcium oxide, zinc oxide and calcium hydroxide.
[0048] In the present invention, the vulcanizing agent can be a conventional choice in the art. In a specific embodiment, in the raw material composition, the vulcanizing agent is selected from one or more of N,N'-biscinnamaldehyde-1,6-hexanediamine, 2,2-(4-hydroxyphenyl)hexafluoropropane, diisopropylbenzene peroxide and 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane.
[0049] In the present invention, the release agent may be a release agent well known to those skilled in the art. In a specific embodiment, in the raw material composition, the release agent is selected from one or more of zinc stearate, ammonium stearate and paraffin.
[0050] In the present invention, the colorant can be a colorant known to those skilled in the art, as long as it can color the composite film. In a specific embodiment, in the raw material composition, the colorant is selected from one or more of iron red, colloidal graphite and carbon black.
[0051] In the present invention, in order to improve the yield recovery performance of the fluororubber composite material layer and thus reduce the leakage of the breathing valve, it is necessary to reasonably control the amount of the fluororubber, the inorganic filler, the acid absorber, the vulcanizer, the release agent and the colorant.
[0052] In the present invention, in a specific embodiment, in the raw material composition, the weight ratio of the fluororubber, the inorganic filler, the chopped fibers, the acid absorber, the vulcanizing agent, the release agent and the colorant can be 100:10-60:0.001-20:0.001-5:0.2-2:0.001-3.
[0053] In the present invention, whether to add a vulcanization accelerator to the raw materials for preparing the fluororubber composite material layer is selected according to actual needs. In a specific embodiment, the raw material composition also contains a vulcanization accelerator. In a preferred embodiment, the weight ratio of the fluororubber to the vulcanization accelerator is 100:0.001 to 2, such as 100:0.001, 100:0.1, 100:0.2, 100:0.5, 100:0.6, 100:0.7, 100:0.8, 100:0.9 or 100:1. Specifically, the vulcanization accelerator is benzyltriphenylphosphonium chloride and / or triallyl isocyanurate.
[0054] In the invention, in order to meet the basic use requirements, the thickness of the polymer sheet and the fluororubber composite material layer need to meet a certain relationship. In a specific embodiment, the thickness of the fluororubber composite material layer is equivalent to the thickness of the polymer sheet, or the thickness of the fluororubber composite material layer is thicker than the polymer sheet. In a preferred embodiment, the ratio of the thickness of the polymer sheet to the fluororubber composite material layer is 1:1 to 4, for example, 1:1, 1:1.2, 1:1.4, 1:1.5, 1:1.6, 1:1.8, 1:2, 1:2.2, 1:2.4, 1:2.5, 1:2.6, 1:2.8, 1:3, 1:3.2, 1:3.4, 1:3.6, 1:3.8 or 1:4.
[0055] The second aspect of the present invention provides a method for preparing the composite membrane of the breathing valve described in the first aspect, such as Figure 1 As shown, the method includes:
[0056] (1) Preparation of fluororubber composite material: kneading the raw material composition, and then refining the obtained product multiple times to obtain a fluororubber composite material;
[0057] (2) Preparation of composite membrane:
[0058] The polymer sheet and the fluororubber composite material are thermally bonded and then vulcanized to obtain a composite diaphragm.
[0059] The method of the present invention first prepares a fluororubber composite material by mixing and refining, and then thermally bonds and vulcanizes a polymer sheet and the fluororubber composite material to bond the fluororubber composite material and the polymer sheet to obtain a composite membrane including a fluororubber composite material layer and a polymer sheet layer.
[0060] In the present invention, the mixing process can be carried out according to conventional operations in the art. In a preferred embodiment, in step (1), the mixing temperature can be 50 to 80°C, such as 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C. In a preferred embodiment, in step (1), the mixing time can be 15 to 60 minutes, such as 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes or 60 minutes. In a preferred embodiment, in step (1), the mixing speed can be 20 to 60 rpm, such as 20 rpm, 25 rpm, 30 rpm, 35 rpm, 40 rpm, 45 rpm, 50 rpm, 55 rpm or 60 rpm. In the present invention, the mixing is carried out using a mixer of the BL-6175-B model of Baisheng Company.
[0061] In the method of the present invention, the refining process can be carried out according to conventional operations in the art. In a preferred embodiment, in step (1), the refining temperature is 100-140°C, such as 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C or 140°C. In a preferred embodiment, in step (1), the number of refining times is 10 times, 15 times, 20 times, 25 times or 30 times. In a preferred embodiment, the roller spacing is 0.2-4mm, such as 0.2mm, 0.5mm, 1mm, 1.5mm, 2mm, 2.5mm, 3mm, 3.5mm or 4mm. In the present invention, the refining is carried out using a mixer of model MRM480 of Meissen Machinery Company. In the present invention, refining once means that the roller rolls one circle from the mixed raw material.
[0062] In the method of the present invention, the thermal bonding may be a conventional choice in the art. In a preferred embodiment, in step (2), the thermal bonding temperature is 150-160°C, such as 150°C, 151°C, 152°C, 153°C, 154°C, 155°C, 156°C, 157°C, 158°C, 159°C or 160°C. In a preferred embodiment, in step (2), the thermal bonding time is 1-10 min, such as 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min or 10 min.
[0063] In the method of the present invention, the vulcanization process can be carried out according to conventional operations in the art. In order to make the diaphragm have a good yield deformation in the leakage interval from above 0.75 times the opening pressure of the breathing valve to below the opening pressure, and further reduce the leakage of the breathing valve, the vulcanization conditions can be controlled within an appropriate range. In a preferred embodiment, in step (2), the vulcanization temperature can be 180 to 240°C, for example, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C or 240°C. In a preferred embodiment, in step (2), the vulcanization time is 8 to 24h. For example, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h or 24h.
[0064] In a specific embodiment, the method for preparing the breathing valve composite membrane comprises the following steps:
[0065] (1) Preparation of fluororubber composite material: fluororubber, inorganic filler, chopped fibers, acid absorber, vulcanizing agent, mold release agent and colorant are mixed at a temperature of 50 to 80° C., a mixing time of 15 to 60 min, a rotation speed of 20 to 60 rpm, and a weight ratio of the fluororubber, inorganic filler, chopped fibers, acid absorber, vulcanizing agent, mold release agent and colorant of 100:10 to 60:10 to 30:0.001 to 20:0.001 to 5:0.2 to 2:0.001 to 3, and then the obtained product is refined for 10 to 30 times, the refining temperature is 100 to 140° C., and the roller distance is 0.2 to 4 mm, to obtain a fluororubber composite material;
[0066] (2) Preparation of composite membrane:
[0067] The polymer sheet with a thickness of 0.1 to 1 mm and the fluororubber composite material are thermally bonded at a temperature of 150 to 160° C. for 1 to 10 minutes, and then vulcanized at a temperature of 180 to 240° C. for 8 to 24 hours to obtain a composite membrane.
[0068] In another specific embodiment, the method for preparing the breathing valve composite membrane comprises the following steps:
[0069] (1) Preparation of fluororubber composite material: fluororubber, inorganic filler, chopped fibers, acid absorber, vulcanizing agent, mold release agent, colorant and vulcanization accelerator are mixed at a temperature of 50 to 80° C., a mixing time of 15 to 60 min, a rotation speed of 20 to 60 rpm, and a weight ratio of the fluororubber, inorganic filler, chopped fibers, acid absorber, vulcanizing agent, mold release agent and colorant of 100:10 to 60:10 to 30:0.001 to 20:0.001 to 5:0.2 to 2:0.001 to 3:0.001 to 2, and then the obtained product is refined for 10 to 30 times, the refining temperature is 100 to 140° C., and the roller distance is 0.2 to 4 mm, to obtain a fluororubber composite material;
[0070] (2) Preparation of composite membrane:
[0071] The polymer sheet with a thickness of 0.1 to 1 mm and the fluororubber composite material are thermally bonded at a temperature of 150 to 160° C. for 1 to 10 minutes, and then vulcanized at a temperature of 180 to 240° C. for 8 to 24 hours to obtain a composite membrane.
[0072] The third aspect of the present invention provides a super breathing valve composite diaphragm prepared by the method described above. The breathing valve composite diaphragm prepared by the method described in the present invention has a low valve leakage and good high temperature resistance.
[0073] The fourth aspect of the present invention provides the use of the composite diaphragm described in the first aspect or the composite diaphragm described in the third aspect as a breathing valve sealing material.
[0074] The present invention will be described in detail below through examples, but the protection scope of the present invention is not limited thereto.
[0075] In the present invention, the fluororubber 246 is purchased from LG Company of South Korea, with a density of 1.5 g / cm 3 , tensile strength 450kg / cm 2 The fluororubber 26 was purchased from Shandong Huaxia Shenzhou Company, with a density of 1.8g / cm 3 , tensile strength 135kg / cm 2 .
[0076] Example 1
[0077] (1) Preparation of fluororubber composite materials:
[0078] Fluororubber (10 kg of fluororubber 246), inorganic filler (6 kg of aluminum silicate), chopped fibers (1 kg of aramid fibers with a length of 1 mm), acid absorbent (1 kg of calcium oxide), vulcanizing agent (0.2 kg of N,N'-dicinnamaldehyde-1,6-hexanediamine), mold release agent (0.02 kg of zinc stearate) and colorant (0.3 kg of colloidal graphite) were added into a mixer for mixing at a speed of 60 rpm, a temperature of 60°C and a time of 15 min; the obtained product was then refined 10 times at a roller distance of 0.2 mm and a roller temperature of 140°C to obtain a fluororubber composite material;
[0079] (2) Preparation of composite membrane:
[0080] The fluororubber composite material was spread on a 0.1 mm thick PEEK polymer sheet and thermally bonded at a temperature of 160°C for 1 min to obtain a pre-vulcanized composite diaphragm. The diaphragm was then vulcanized at 240°C for 8 h to obtain a composite diaphragm A1 including a 0.2 mm fluororubber composite material layer and a 0.1 mm PEEK polymer sheet layer.
[0081] Example 2
[0082] (1) Preparation of fluororubber composite materials:
[0083] Fluororubber (10 kg of fluororubber 26), inorganic filler (0.5 kg of white carbon black, 0.3 kg of calcium silicate, 0.1 kg of magnesium silicate and 0.1 kg of boron nitride), chopped fibers (1 kg of 5 mm glass fiber and 2 kg of 2 mm carbon fiber), acid absorbent (1 kg of magnesium oxide), vulcanizing agent (0.5 kg of N, N'-biscinnamaldehyde-1,6-hexanediamine), release agent (0.02 kg of paraffin wax) and colorant (0.2 kg of iron red) are added into a mixer for mixing, wherein the mixing speed is 20 rpm, the temperature is 80°C and the time is 60 min; then the obtained product is refined 20 times with a roller distance of 2 mm and a roller temperature of 100°C to obtain a fluororubber composite material;
[0084] (2) Preparation of composite membrane:
[0085] The fluororubber composite material is spread on a 0.5 mm thick PTFE polymer sheet and thermally bonded at a temperature of 150°C for 10 min to obtain a pre-vulcanized composite diaphragm. The diaphragm is then vulcanized at 180°C for 24 h to obtain a composite diaphragm A2 including a 2 mm fluororubber composite material layer and a 0.5 mm PTFE polymer sheet layer.
[0086] Example 3
[0087] (1) Preparation of fluororubber composite materials:
[0088] Fluororubber (10 kg of fluororubber 246), inorganic filler (1 kg of calcium carbonate, 1 kg of diatomaceous earth, 0.5 kg of calcium silicate and 0.1 kg of graphite), chopped fibers (0.5 kg of 2 mm ceramic fiber and 1.5 kg of 3 mm glass fiber), acid absorbent (1 kg of calcium hydroxide), vulcanizing agent (0.02 kg of 2,2-(4-hydroxyphenyl)hexafluoropropane), vulcanization accelerator (0.02 kg of benzyltriphenylphosphonium chloride), release agent (0.02 kg of ammonium stearate) and colorant (0.03 kg of iron oxide red) are added into a mixer for mixing, wherein the mixing speed is 30 rpm, the temperature is 70°C and the time is 40 min; then the obtained product is refined 30 times with a roller distance of 4 mm and a roller temperature of 120°C to obtain a fluororubber composite material;
[0089] (2) Preparation of composite membrane:
[0090] The fluororubber composite material was spread on a 1 mm thick PI polymer sheet and thermally bonded at a temperature of 150°C for 5 minutes to obtain a pre-vulcanized composite membrane. The membrane was then vulcanized at 200°C for 16 hours to obtain a composite membrane A3 including a 4 mm fluororubber composite material layer and a 1 mm PI polymer sheet layer.
[0091] Example 4
[0092] (1) Preparation of fluororubber composite materials:
[0093] Fluororubber (10 kg of fluororubber 26), inorganic filler (4 kg of aluminum silicate, 1 kg of barium sulfate, 0.05 kg of silicon nitride and 0.2 kg of graphite), chopped fibers (1 kg of 1 mm aramid fiber and 1 kg of 2 mm glass fiber), acid absorbent (1 kg of calcium oxide and 0.5 kg of calcium hydroxide), vulcanizing agent (0.01 kg of diisopropylbenzene peroxide), vulcanization accelerator (0.01 kg of triallyl isocyanurate), release agent (0.02 kg of paraffin wax) and colorant (0.2 kg of iron oxide red) are added into a mixer for mixing, wherein the mixing speed is 40 rpm, the temperature is 65° C. and the time is 30 min; then the obtained product is refined 30 times with a roller distance of 0.5 mm and a roller temperature of 130° C. to obtain a fluororubber composite material;
[0094] (2) Preparation of composite membrane:
[0095] The fluororubber composite material is spread on a 0.6 mm thick PTFE polymer sheet and thermally bonded at a temperature of 160°C for 7 minutes to obtain a pre-vulcanized composite diaphragm. The diaphragm is then vulcanized at 220°C for 12 hours to obtain a composite diaphragm A4 including a 0.6 mm fluororubber composite material layer and a 0.6 mm PTFE polymer sheet layer.
[0096] Example 5
[0097] (1) Preparation of fluororubber composite materials:
[0098] Fluororubber (10 kg of fluororubber 246), inorganic filler (1 kg of calcium silicate, 1 kg of magnesium silicate, 0.5 kg of calcium carbonate and 0.1 kg of graphite), chopped fibers (1.5 kg of 2 mm aramid fibers), acid absorbent (0.5 kg of calcium oxide and 0.5 kg of calcium hydroxide), vulcanizing agent (0.01 kg of 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane), vulcanization accelerator (0.01 kg of triallyl isocyanurate), release agent (0.01 kg of paraffin wax) and colorant (0.15 kg of iron oxide red) are added into a mixer for mixing at a rotation speed of 50 rpm, a temperature of 70°C and a time of 30 min; the obtained product is then refined 30 times at a roller distance of 1 mm and a roller temperature of 140°C to obtain a fluororubber composite material;
[0099] (2) Preparation of composite membrane:
[0100] The fluororubber composite material was spread on a 0.5 mm thick PTFE polymer sheet and thermally bonded at a temperature of 160°C for 10 min to obtain a pre-vulcanized composite diaphragm. The diaphragm was then vulcanized at 240°C for 16 h to obtain a composite diaphragm A5 including a 2 mm fluororubber composite material layer and a 0.5 mm PTFE polymer sheet layer.
[0101] Example 6
[0102] The method of Example 5 is used, except that the inorganic filler is 0.5 kg of white carbon black, 1 kg of silicon nitride and 1.1 kg of boron nitride. The specific operation is as follows:
[0103] (1) Preparation of fluororubber composite materials:
[0104] Fluororubber (10 kg of fluororubber 246), inorganic filler (0.5 kg of white carbon black, 1 kg of silicon nitride and 1 kg of boron nitride), chopped fibers (1.5 kg of 2 mm aramid fibers), acid absorbent (0.5 kg of calcium oxide and 0.5 kg of calcium hydroxide), vulcanizing agent (0.01 kg of 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane), vulcanization accelerator (0.01 kg of triallyl isocyanurate), release agent (0.01 kg of paraffin wax) and colorant (0.15 kg of iron oxide red) are added into a mixer for mixing at a speed of 50 rpm, a temperature of 70°C and a time of 30 min; the obtained product is then refined 30 times at a roller distance of 1 mm and a roller temperature of 140°C to obtain a fluororubber composite material;
[0105] (2) Preparation of composite membrane:
[0106] The fluororubber composite material was spread on a 0.5 mm thick PTFE polymer sheet and thermally bonded at a temperature of 160°C for 10 min to obtain a pre-vulcanized composite diaphragm. The diaphragm was then vulcanized at 240°C for 16 h to obtain a composite diaphragm A6 including a 1 mm fluororubber composite material layer and a 0.5 mm PTFE polymer sheet layer.
[0107] Example 7
[0108] The method of Example 5 was followed, except that the inorganic filler was 1 kg of aluminum silicate and 1.6 kg of diatomaceous earth. The specific operation was as follows:
[0109] (1) Preparation of fluororubber composite materials:
[0110] Fluororubber (10 kg of fluororubber 246), inorganic filler (1 kg of aluminum silicate and 1.6 kg of diatomaceous earth), chopped fibers (1.5 kg of 2 mm aramid fibers), acid absorbent (0.5 kg of calcium oxide and 0.5 kg of calcium hydroxide), vulcanizing agent (0.01 kg of 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane), vulcanization accelerator (0.01 kg of triallyl isocyanurate), release agent (0.01 kg of paraffin wax) and colorant (0.15 kg of iron oxide red) are added into a mixer for mixing, wherein the mixing speed is 50 rpm, the temperature is 70°C, and the time is 30 minutes; then the obtained product is refined 30 times, the roller distance is 1 mm, and the roller temperature is 140°C, to obtain a fluororubber composite material;
[0111] (2) Preparation of composite membrane:
[0112] The fluororubber composite material is spread on a 0.5 mm thick PTFE polymer sheet and thermally bonded at a temperature of 160°C for 10 minutes to obtain a pre-vulcanized composite diaphragm. The diaphragm is then vulcanized at 240°C for 16 hours to obtain a composite diaphragm A7 including a 1 mm fluororubber composite material layer and a 0.5 mm PTFE polymer sheet layer.
[0113] Example 8
[0114] The method of Example 5 was followed, except that no vulcanization accelerator was added. The specific operation was as follows:
[0115] (1) Preparation of fluororubber composite materials:
[0116] Fluororubber (10 kg of fluororubber 246), inorganic filler (1 kg of calcium silicate, 1 kg of magnesium silicate, 0.5 kg of calcium carbonate and 0.1 kg of graphite), chopped fibers (1.5 kg of 2 mm aramid fibers), acid absorbent (0.5 kg of calcium oxide and 0.5 kg of calcium hydroxide), vulcanizing agent (0.01 kg of 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane), mold release agent (0.01 kg of paraffin wax) and colorant (0.15 kg of iron oxide red) were added into a mixer for mixing at a speed of 50 rpm, a temperature of 70°C and a time of 30 min; the obtained product was refined 30 times at a roller distance of 1 mm and a roller temperature of 140°C to obtain a fluororubber composite material;
[0117] (2) Preparation of composite membrane:
[0118] The fluororubber composite material is spread on a 0.5 mm thick PTFE polymer sheet and thermally bonded at a temperature of 160°C for 10 minutes to obtain a pre-vulcanized composite diaphragm. The diaphragm is then vulcanized at 240°C for 16 hours to obtain a composite diaphragm A8 including a 1 mm fluororubber composite material layer and a 0.5 mm PTFE polymer sheet layer.
[0119] Example 9
[0120] The method of Example 5 is used, except that the vulcanization temperature is 190° C. The specific operation is as follows:
[0121] (1) Preparation of fluororubber composite materials:
[0122] Fluororubber (10 kg of fluororubber 246), inorganic filler (1 kg of calcium silicate, 1 kg of magnesium silicate, 0.5 kg of calcium carbonate and 0.1 kg of graphite), chopped fibers (1.5 kg of 2 mm aramid fibers), acid absorbent (0.5 kg of calcium oxide and 0.5 kg of calcium hydroxide), vulcanizing agent (0.01 kg of 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane), vulcanization accelerator (0.01 kg of triallyl isocyanurate), release agent (0.01 kg of paraffin wax) and colorant (0.15 kg of iron oxide red) are added into a mixer for mixing at a rotation speed of 50 rpm, a temperature of 70°C and a time of 30 min; the obtained product is then refined 30 times at a roller distance of 1 mm and a roller temperature of 140°C to obtain a fluororubber composite material;
[0123] (2) Preparation of composite membrane:
[0124] The fluororubber composite material is spread on a 0.5 mm thick PTFE polymer sheet and thermally bonded at a temperature of 160°C for 10 minutes to obtain a pre-vulcanized composite diaphragm. The diaphragm is then vulcanized at 190°C for 16 hours to obtain a composite diaphragm A9 including a 1 mm fluororubber composite material layer and a 0.5 mm PTFE polymer sheet layer.
[0125] Example 10
[0126] The method of Example 5 is used, except that the thickness of the PTFE polymer sheet is 0.8 mm. The specific operation is as follows:
[0127] (1) Preparation of fluororubber composite materials:
[0128] Fluororubber (10 kg of fluororubber 246), inorganic filler (1 kg of calcium silicate, 1 kg of magnesium silicate, 0.5 kg of calcium carbonate and 0.1 kg of graphite), chopped fibers (1.5 kg of 2 mm aramid fibers), acid absorbent (0.5 kg of calcium oxide and 0.5 kg of calcium hydroxide), vulcanizing agent (0.01 kg of 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane), vulcanization accelerator (0.01 kg of triallyl isocyanurate), release agent (0.01 kg of paraffin wax) and colorant (0.15 kg of iron oxide red) are added into a mixer for mixing at a rotation speed of 50 rpm, a temperature of 70°C and a time of 30 min; the obtained product is then refined 30 times at a roller distance of 1 mm and a roller temperature of 140°C to obtain a fluororubber composite material;
[0129] (2) Preparation of composite membrane:
[0130] The fluororubber composite material was spread on a 0.8 mm thick PTFE polymer sheet and thermally bonded at a temperature of 160°C for 10 min to obtain a pre-vulcanized composite diaphragm. The diaphragm was then vulcanized at 240°C for 16 h to obtain a composite diaphragm A10 including a 1 mm fluororubber composite material layer and a 0.8 mm PTFE polymer sheet layer.
[0131] Comparative Example 1
[0132] The method of Example 5 is used, except that the thickness of the PTFE polymer sheet is 1.5 mm. The specific operation is as follows:
[0133] (1) Preparation of fluororubber composite materials:
[0134] Fluororubber (10 kg of fluororubber 246), inorganic filler (1 kg of calcium silicate, 1 kg of magnesium silicate, 0.5 kg of calcium carbonate and 0.1 kg of graphite), chopped fibers (1.5 kg of 2 mm aramid fibers), acid absorbent (0.5 kg of calcium oxide and 0.5 kg of calcium hydroxide), vulcanizing agent (0.01 kg of 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane), vulcanization accelerator (0.01 kg of triallyl isocyanurate), release agent (0.01 kg of paraffin wax) and colorant (0.15 kg of iron oxide red) are added into a mixer for mixing at a rotation speed of 50 rpm, a temperature of 70°C and a time of 30 min; the obtained product is then refined 30 times at a roller distance of 1 mm and a roller temperature of 140°C to obtain a fluororubber composite material;
[0135] (2) Preparation of composite membrane:
[0136] The fluororubber composite material was spread on a 1.5 mm thick PTFE polymer sheet and thermally bonded at a temperature of 160°C for 10 min to obtain a pre-vulcanized composite diaphragm. The diaphragm was then vulcanized at 240°C for 16 h to obtain a composite diaphragm B1 including a 2 mm fluororubber composite material layer and a 1.5 mm PTFE polymer sheet layer.
[0137] Comparative Example 2
[0138] The method of Example 5 was followed, except that nitrile rubber (purchased from LG, South Korea, with a brand name of LGB3250) was used to replace the fluororubber. The specific operation was as follows:
[0139] (1) Preparation of nitrile rubber composite materials:
[0140] Adding nitrile rubber (10 kg of nitrile rubber), inorganic filler (1 kg of calcium silicate, 1 kg of magnesium silicate, 0.5 kg of calcium carbonate and 0.1 kg of graphite), chopped fibers (1.5 kg of 2 mm aramid fibers), acid absorbent (0.5 kg of calcium oxide and 0.5 kg of calcium hydroxide), vulcanizing agent (0.01 kg of 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane), vulcanization accelerator (0.01 kg of triallyl isocyanurate), release agent (0.01 kg of paraffin wax) and colorant (0.15 kg of iron red) into a mixer for mixing, wherein the mixing speed is 50 rpm, the temperature is 70°C, and the time is 30 minutes; then refining the obtained product 30 times, with a roller distance of 1 mm and a roller temperature of 140°C, to obtain a nitrile rubber composite material;
[0141] (2) Preparation of composite membrane:
[0142] The nitrile rubber composite material is spread on a 0.5 mm thick PTFE polymer sheet and thermally bonded at a temperature of 160°C for 10 minutes to obtain a pre-vulcanized composite diaphragm. The diaphragm is then vulcanized at 240°C for 16 hours to obtain a composite diaphragm B2 including a 2 mm nitrile rubber composite material layer and a 0.5 mm PTFE polymer sheet layer.
[0143] Comparative Example 3
[0144] The method of Example 5 is used, except that no chopped fibers are added during the preparation of the fluororubber composite material. The specific operation is as follows:
[0145] (1) Preparation of fluororubber composite materials:
[0146] Fluororubber (10 kg of fluororubber 246), inorganic filler (1 kg of calcium silicate, 1 kg of magnesium silicate, 0.5 kg of calcium carbonate and 0.1 kg of graphite), acid absorber (0.5 kg of calcium oxide and 0.5 kg of calcium hydroxide), vulcanizing agent (0.01 kg of 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane), vulcanization accelerator (0.01 kg of triallyl isocyanurate), release agent (0.01 kg of paraffin wax) and colorant (0.15 kg of iron oxide red) are added into a mixer for mixing, wherein the mixing speed is 50 rpm, the temperature is 70°C and the time is 30 minutes; then the obtained product is refined 30 times with a roller distance of 1 mm and a roller temperature of 140°C to obtain a fluororubber composite material;
[0147] (2) Preparation of composite membrane:
[0148] The fluororubber composite material was spread on a 0.5 mm thick PTFE polymer sheet and thermally bonded at a temperature of 160°C for 10 min to obtain a pre-vulcanized composite diaphragm. The diaphragm was then vulcanized at 240°C for 16 h to obtain a composite diaphragm B3 including a 2 mm fluororubber composite material layer and a 0.5 mm PTFE polymer sheet layer.
[0149] Comparative Example 4
[0150] The method of Example 1 is followed, except that the fluororubber composite material does not use chopped fibers.
[0151] (1) Preparation of fluororubber composite materials:
[0152] Fluororubber (10 kg of fluororubber 246), inorganic filler (6 kg of aluminum silicate), acid absorber (1 kg of calcium oxide), vulcanizing agent (0.2 kg of N,N'-biscinnamaldehyde-1,6-hexanediamine), mold release agent (0.02 kg of zinc stearate) and colorant (0.3 kg of colloidal graphite) are added into a mixer for mixing at a speed of 60 rpm, a temperature of 60°C and a time of 15 min; then the obtained product is refined 10 times at a roller distance of 0.2 mm and a roller temperature of 140°C to obtain a fluororubber composite material;
[0153] (2) Preparation of composite membrane:
[0154] The fluororubber composite material was spread on a 0.1 mm thick PEEK polymer sheet and thermally bonded at a temperature of 160°C for 1 min to obtain a pre-vulcanized composite diaphragm. The diaphragm was then vulcanized at 240°C for 8 h to obtain a composite diaphragm B4 including a 0.2 mm fluororubber composite material layer and a 0.1 mm PEEK polymer sheet layer.
[0155] Test Example 1
[0156] The maximum leakage of the composite materials prepared in the test examples and comparative examples is shown in Table 1. The test method is:
[0157] The composite diaphragms A1-A10, B1-B4 prepared in the embodiments and comparative examples are cut after standing to obtain diaphragms 1a-10a, B1a, B2a, B3a, B4a matching breathing valves with a nominal diameter of 150 mm, and diaphragms 1b-10b, B1b, B2b, B3b, B4b matching breathing valves with a nominal diameter of 200 mm. Place it in an environment of 20℃ and 60% humidity for 24h, and test it according to SY / T0511-2010 8.6 leakage test. The specific process is: install the composite diaphragm on the valve disc of the breathing valve with different nominal diameters, and the valve disc weight is 1350Pa. Then install the breathing valve on the breathing valve test platform, adjust the pressure to 1012Pa (0.75 times the opening pressure), measure the leakage of the breathing valve, count the value once every minute, for a total of three times, take the arithmetic mean, that is, the leakage of the tank breathing valve when the pressure is not less than 0.75 times the opening pressure (1012Pa).
[0158] Table 1
[0159]
[0160]
[0161] Test Example 2
[0162] The high temperature resistance of the composite membranes prepared in Examples 1 and 5 and Comparative Examples 3 and 4 was tested, and the results are shown in Table 2. The high temperature resistance was measured according to the following method:
[0163] According to the requirements of GB / T 528-2009, the composite membranes A1 and A5 prepared in Examples 1 and 5 and the composite membranes B3 and B4 prepared in Comparative Examples 3 and 4 were cut into 2-type dumbbell specimens, several in number. The four specimens were placed in an air oven at 80°C, 100°C, and 120°C, respectively, and heated for 48 hours, 96 hours, and 168 hours, and their tensile strength, tensile strength change rate, elongation at break, and elongation at break change rate were tested.
[0164] Table 2
[0165]
[0166]
[0167] As can be seen from Table 1, the breathing valve composite diaphragm is prepared according to the method of the embodiment, and the breathing valve leakage is low; in comparative example 1, the thickness of the PTFE polymer sheet is too thick, and the breathing valve leakage is significantly increased; in comparative example 2, the nitrile rubber is replaced with fluororubber, and the breathing valve leakage is significantly increased; in comparative examples 3 and 4, no chopped fibers are added, and the breathing valve leakage is equivalent to that of the embodiments.
[0168] From the results in Table 2, it can be seen that the tensile strength of the composite membranes prepared in Example 1 and Example 5 increased from a maximum of 11.8 N / mm to a maximum of 11.8 N / mm under continuous heating at a temperature of 80°C to 120°C for 48h to 168h. 2 Reduced to a minimum of 10.5N / mm 2 The tensile strength change rate was 0-11.0%, the elongation at break increased from 199% to a maximum of 217%, and the elongation at break change rate increased from 0 to a maximum of 11.0%. The composite membranes prepared in Comparative Examples 3 and 4 had a tensile strength of 9.7 N / mm at a temperature of 80°C to 120°C and a continuous heating time of 48h to 168h. 2 Reduced to a minimum of 6.3N / mm 2 , the change rate of tensile strength is 1.0% to 25.3%, the elongation at break increases from 234% to a maximum of 292%, and the change rate of elongation at break increases from 0.4% to a maximum of 25.3%. It can be seen that under high temperature conditions, the tensile strength of the composite membranes prepared in Examples 1 and 5 is higher than that of the composite membranes prepared in Comparative Examples 3 and 4, and the elongation at break is lower, that is, the composite membranes prepared in the embodiments have better high temperature resistance than the composite membranes prepared in Comparative Examples 3 and 4.
[0169] Therefore, the composite diaphragm obtained by adopting the technical solution of the present invention has a low leakage of the breathing valve above 0.75 times the opening pressure of the breathing valve to below the opening pressure, and has good high temperature resistance.
[0170] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A composite diaphragm for a breathing valve, characterized in that: The breathing valve composite diaphragm comprises a polymer layer and a fluororubber composite material layer. Wherein, the thickness of the polymer sheet is 0.1 to 1 mm; The fluororubber composite material layer is prepared from a raw material composition containing fluororubber, inorganic filler, chopped fibers, an acid absorbent, a vulcanizing agent, a release agent and a colorant.
2. The breathing valve composite diaphragm according to claim 1, characterized in that: The polymer sheet material forming the polymer sheet layer is selected from one or more of polyetheretherketone, polytetrafluoroethylene and polyimide.
3. The breathing valve composite diaphragm according to claim 1 or 2, characterized in that: In the raw material composition, the fluororubber is 26-type fluororubber and / or 246-type fluororubber.
4. The breathing valve composite diaphragm according to any one of claims 1 to 3, characterized in that: In the raw material composition, the inorganic filler is selected from one or more of white carbon black, calcium silicate, magnesium silicate, aluminum silicate, calcium carbonate, barium sulfate, diatomaceous earth, graphite, silicon nitride and boron nitride.
5. The breathing valve composite diaphragm according to any one of claims 1 to 4, characterized in that: In the raw material composition, the chopped fibers are selected from one or more of aramid fibers, glass fibers, carbon fibers and ceramic fibers; Preferably, the length of the chopped fibers is 1 to 5 mm.
6. The breathing valve composite diaphragm according to any one of claims 1 to 5, characterized in that: In the raw material composition, the acid absorber is selected from one or more of magnesium oxide, calcium oxide, zinc oxide and calcium hydroxide.
7. The breathing valve composite diaphragm according to any one of claims 1 to 6, characterized in that: In the raw material composition, the vulcanizing agent is selected from one or more of N,N'-dicinnamaldehyde-1,6-hexanediamine, 2,2-(4-hydroxyphenyl)hexafluoropropane, diisopropylbenzene peroxide and 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane.
8. The breathing valve composite diaphragm according to any one of claims 1 to 7, characterized in that: In the raw material composition, the release agent is selected from one or more of zinc stearate, ammonium stearate and paraffin.
9. The breathing valve composite diaphragm according to any one of claims 1 to 8, characterized in that: In the raw material composition, the colorant is selected from one or more of iron red, colloidal graphite and carbon black.
10. The breathing valve composite diaphragm according to any one of claims 1 to 9, characterized in that: In the raw material composition, the weight ratio of the fluororubber, the inorganic filler, the chopped fibers, the acid absorber, the vulcanizing agent, the release agent and the colorant is 100:10-60:10-30:0.001-20:0.001-5:0.2-2:0.001-3.
11. The breathing valve composite diaphragm according to any one of claims 1 to 10, characterized in that: The raw material composition also contains a vulcanization accelerator; Preferably, the weight ratio of the fluororubber to the vulcanization accelerator is 100:0.001-2; Preferably, the vulcanization accelerator is benzyltriphenylphosphonium chloride and / or triallyl isocyanurate.
12. The breathing valve composite diaphragm according to any one of claims 1 to 11, characterized in that: The thickness ratio of the polymer sheet layer to the fluororubber composite material layer is 1:1-4.
13. A method for preparing the composite membrane of a breathing valve according to any one of claims 1 to 12, characterized in that: The method includes: (1) Preparation of fluororubber composite material: kneading the raw material composition, and then refining the obtained product multiple times to obtain a fluororubber composite material; (2) Preparation of composite membrane: The polymer sheet and the fluororubber composite material are thermally bonded and then vulcanized to obtain a composite diaphragm.
14. The method according to claim 13, characterized in that In step (1), the mixing conditions include: temperature of 50 to 80° C., time of 15 to 60 min, and rotation speed of 20 to 60 rpm.
15. The method according to claim 13 or 14, characterized in that In step (1), the refining conditions include: a temperature of 100 to 140° C., a refining frequency of 10 to 30 times, and a roller distance of 0.2 to 4 mm.
16. The method according to any one of claims 13 to 15, characterized in that: In step (2), the thermal bonding conditions include: a temperature of 150 to 160° C. and a time of 1 to 10 minutes.
17. The method according to any one of claims 13 to 16, characterized in that: In step (2), the vulcanization conditions include: temperature of 180 to 240° C. and time of 8 to 24 hours.
18. A composite membrane for a breathing valve prepared by the method according to any one of claims 13 to 17.
19. Use of the breathing valve composite diaphragm according to any one of claims 1 to 12 or the breathing valve composite diaphragm according to claim 18 as a breathing valve sealing material.
Citation Information
Patent Citations
Polyphenyl thioether sheet with electrical insulation properties and preparation method thereof
CN103087524A
Fluororubber for valves and preparation method thereof
CN115584093A
laminate
WO2012081413A1
Vibration diaphragm for miniature sound-producing device and miniature sound-producing device
WO2021082239A1